Effect of climate change, extreme temperatures (heat and cold) on diabetes mellitus risk, hospitalization, and mortality: Global Evidenced Based Study - Meo, Sultan Ayoub; Shaikh, Narmeen; Abukhalaf, Farah Adnan; Meo, Anusha Sultan; Klonoff, David C. (Frontiers in Public Health, 2025)
BackgroundClimate change and diabetes mellitus are challenging threats to humanity in the 21st century. Climate change enhances the occurrence and severity of extreme temperature events, heat and cold, which can lead to severe health consequences. This study aimed to investigate the effects of extreme temperatures, including heat and cold, on the risk of developing diabetes mellitus, requiring hospitalizations or emergency department (ED) visits, and deaths.MethodsIn this study, 116 documents were initially identified from “databases, including PubMed, Web of Science, Scopus, and Google Scholar.” Articles on extreme temperatures, heat, cold, and diabetes mellitus were searched using the keywords: climate change, extreme temperatures, heat, cold, and diabetes mellitus. The descriptive information was recorded from the identified studies. Eventually, 13 documents were included in the analysis and synthesis. The association between extreme temperatures, including heat and cold, and diabetes-related outcomes, such as diabetes risk, hospitalizations, ED visits, and mortality was established.ResultsExposure to extreme temperatures (heat and cold) were positively and significantly related with an increased risk of adverse diabetes-related events, with a combined risk ratio (RR) of 1.14 (95% CI: 1.08–1.21, p = 0.01); diabetes-related hospitalizations and emergency department (ED) visits (RR of 1.10, 95% CI: 1.01–1.19, p = 0.03); and increased diabetes-linked mortality (RR 1.16, 95% CI: 1.07–1.25, p = 0.01).ConclusionsExtreme temperatures (heat and cold) significantly increased adverse diabetes-related events, hospitalizations, emergency department visits, and diabetes-related mortality. Reducing the risk of climate change and extreme temperatures requires coordinated efforts at individual, community, national and global levels to combat climate change and diabetes mellitus.